The Relationship Of Mother's Knowledge And Characteristics On The Slowness Of The Process Of Early Breastfeeding Initiation in the Practiceof Midwifer Feronika Hutajulu - Parhusip, Drima Yance; Azelina, Dina; Qamallia, Dita; Sari, Duma Indah Fatika; Simanjuntak, Dwita Dahlia (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2024)
A mother can prevent her baby from dying in the first month of life if she breastfeeds her baby within 60 minutes after birth. However, the lack of knowledge and understanding of parents, doctors or health workers about the importance of IMD, as well as the reluctance to implement IMD, makes its implementation difficult. One of the reasons for the success or failure of IMD lies in the midwife. Because they are the ones who encourage and educate postpartum mothers to implement IMD. This research is included in the type of analytical research using a cross-sectional research design. The general aim of the research is to determine the relationship between maternal characteristics and early breastfeeding practices after giving birth. Meanwhile, specifically, this research seeks to identify the relationship between maternal knowledge, attitudes, age and parity of postpartum mothers who practice early breastfeeding at the Feronika Hutajulu Midwife Practice. Sampling was carried out using a non-probability sampling technique with a total sampling method of 26 people. Data collection uses a questionnaire. From analysis of research data using the chi-square test with a confidence level of 5% (a=0.05) knowledge data had a p value of 0.000, attitude data had a p value of 0.000, age data had a p value of 0.014, and parity data had a p value of 0.020. So it can be concluded that there is a relationship between maternal knowledge, maternal attitude, maternal age and maternal parity on the implementation of IMD.